AHNAK2 Promotes the Progression of Differentiated Thyroid Cancer through PI3K/AKT Signaling Pathway - Xu, Min; Wen, Jialiang; Xu, Qiding; Li, Huihui; Lin, Bangyi; Bhandari, Adheesh; Qu, Jinmiao (Current Cancer Drug Targets, 2024)
Aims: AHNAK2 may be used as a candidate marker for TC diagnosis and treatment. Background: Thyroid cancer (TC) is the most frequent malignancy in endocrine carcinoma, and the incidence has been increasing for decades. Objective: To understand the molecular mechanism of DTC, we performed next-generation sequencing (NGS) on 79 paired DTC tissues and normal thyroid tissues. The RNA-sequencing (RNA-seq) data analysis results indicated that AHNAK nucleoprotein 2 (AHNAK2) was significantly upregulated in the thyroid cancer patient’s tissue. Methods: We also analyzed AHNAK2 mRNA levels of DTC tissues and normal tissues from The Cancer Genome Atlas (TCGA). The association between the expression level of AHNAK2 and clinicopathological features was evaluated in the TCGA cohort. Furthermore, AHNAK2 gene expression was analyzed by quantitative real-time polymerase chain reaction (qRT-PCR) in 40 paired DTC tissues and adjacent normal thyroid tissues. The receiver operating characteristic (ROC) curve was performed to evaluate the diagnostic value of AHNAK2. For cell experiments in vitro, AHNAK2 was knocked down using small interfering RNA (siRNA), and the biological function of AHNAK2 in TC cell lines was investigated. The expression of AHNAK2 was significantly upregulated in both the TCGA cohort and the local cohort. Results: The analysis results of the TCGA cohort indicated that the upregulation of AHNAK2 was associated with tumor size (P < 0.001), lymph node metastasis (P < 0.001), and disease stage (P < 0.001). The area under the curve (AUC, TCGA: P < 0.0001; local validated cohort: P < 0.0001) in the ROC curve revealed that AHNAK2 might be considered a diagnostic biomarker for TC. The knockdown of AHNAK2 reduced TC cell proliferation, colony formation, migration, invasion, cell cycle, and induced cell apoptosis. Conclusion: Furthermore, the protein levels of phospho-PI3 Kinase p85 and phospho-AKT were downregulated in the transfected TC cell. Our study results indicate that AHNAK2 may promote metastasis and proliferation of thyroid cancer through PI3K/AKT signaling pathway. Thus, AHNAK2 may be used as a candidate marker for TC diagnosis and treatment.
Keywords: progression